PESTISIDLARNING TUPROQ BIORESURSLARIGA ZARARLI TA’SIRI - Xaydarova , Zubaydaxon; Eshkarayev , Sadriddin (Theoretical and experimental chemistry and modern problems of chemical technology, 2023)
In the article, 2 types of pesticides, which are relatively common in the soils of Surkhandarya region, get into the human body and their harmful consequences, migration routes, evaporation rate and soil sorption capacity were studied. In particular, the dependence of the evaporation rate on the soil composition was studied.